2018
DOI: 10.1016/j.jcv.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and seasonality of acute respiratory infections in hospitalized children over four consecutive years (2012–2016)

Abstract: our results constitute a detailed description of the distribution of respiratory viruses among hospitalized children over four consecutive years. Our data notably highlight the persistence of non-enveloped viruses and some enveloped viruses throughout the year-regardless of temperature variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…From a total of 288 samples analyzed from children under 5 years old with a probable diagnosis of Pertussis, the most common pathogen isolated was ADV in 49% of samples, followed by B. pertussis in 41% from our previous analysis. Although this study was conducted in patients with ARI with a highly suspicious pertussis diagnosis, other studies on children with ARI have identified ADV as one of the most prevalent etiologies [2] Although, the viral and bacterial prevalence may vary widely depending on the population characteristics [8,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…From a total of 288 samples analyzed from children under 5 years old with a probable diagnosis of Pertussis, the most common pathogen isolated was ADV in 49% of samples, followed by B. pertussis in 41% from our previous analysis. Although this study was conducted in patients with ARI with a highly suspicious pertussis diagnosis, other studies on children with ARI have identified ADV as one of the most prevalent etiologies [2] Although, the viral and bacterial prevalence may vary widely depending on the population characteristics [8,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…BALB/c female mice were placed in six chambers (six mice each) with air temperature of 24 ± 3 C, humidity of 60 ± 4%, and a 12-hours light/dark cycle, but with the subsequent light onset staggered by 4 hours between cameras. Thus the study at one outer test time followed in six test times (2,6,10,14,18, and 22 hours after light onset). Rectal temperature was measured at baseline and 1 hour after oral treatment with placebo or two doses of homeopathic aconite (6C and 30C) in six experimental regimens.…”
Section: Efficacy Profile Of the Homeopathic Productmentioning
confidence: 99%
“…They reach to approximately 90% of all infectious pathologies and re-main one of the most significant medical and socioeconomic problems. On average, over a year, an adult suffers from acute respiratory viral infections at least 2-3 times, while a childup to 6-10 times [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Acute Respiratory Tract Infection (ARI) is an infection that attacks the throat, nose, and lungs which occurs around fourteen days (Kemenkes RI, 2012) and becomes the main cause of death, especially in children around the world (Fillatre et al, 2018). Around 18-33% of the death of children under five years is estimated to be caused by ARI (Khan & Islam, 2017).…”
Section: Introductionmentioning
confidence: 99%